Opening Pandora's box in the UK: a hypothetical pharmacogenetic test for clozapine. (November 2013) - Spencer, Benjamin WJ; Prainsack, Barbara; Rujescu, Dan; Giegling, Ina; Collier, David A; Gaughran, Fiona; MacCabe, James H; Barr, Cathy L; Sigurdsson, Engilbert; Stovring, Henrik; Malhotra, Anil K; Curran, Sarah R
Clozapine is a uniquely efficacious antipsychotic drug in treatment-resistant schizophrenia. Its use is restricted due to adverse effects including a rare but dangerous reduction in neutrophils (agranulocytosis) and the mandatory hematological monitoring this entails in many countries. We review the statistical, ethical and legal issues arising from a hypothetical pharmacogenetic test for clozapine, using the UK as an exemplary case for consideration. Our key findings include: a consideration of the probabilistic results that a pharmacogenetic test may return; the impact on drug licensing; and the potential for pharmacogenetic tests for clozapine being used without consent under the UK's legal framework. We make recommendations regarding regulatory changes applicable to the special case of pharmacogenetic testing in clozapine treatment.